Insulin-like growth factor-I gene therapy reverses morphologic changes and reduces hyperprolactinemia in experimental rat prolactinomas - Cónsole, Gloria Miriam (2008)
Background: The implementation of gene therapy for the treatment of pituitary tumors emerges as a promising complement to surgery and may have distinct advantages over radiotherapy for this type of tumors. Up to now, suicide gene therapy has been the main experimental approach explored to treat experimental pituitary tumors. In the present study we assessed the effectiveness of insulin-like growth factor I (IGF-I) gene therapy for the treatment of estrogen-induced prolactinomas in rats. Results: Female Sprague Dawley rats were subcutaneously implanted with silastic capsules filled with 17-β estradiol (E2) in order to induce pituitary prolactinomas. Blood samples were taken at regular intervals in order to measure serum prolactin (PRL). As expected, serum PRL increased progressively and 23 days after implanting the E2 capsules (Experimental day 0), circulating PRL had undergone a 3-4 fold increase. On Experimental day 0 part of the E2-implanted animals received a bilateral intrapituitary injection of either an adenoviral vector expressing the gene for rat IGF-I (RAd-IGFI), or a vector (RAd-GFP) expressing the gene for green fluorescent protein (GFP). Seven days post vector injection all animals were sacrificed and their pituitaries morphometrically analyzed to evaluate changes in the lactotroph population. RAd-IGFI but not RAd-GFP, induced a significant fall in serum PRL. Furthermore, RAd-IGFI but not RAd-GFP significantly reversed the increase in lactotroph size (CS) and volume density (VD) induced by E2 treatment. Conclusion: We conclude that IGF-I gene therapy constitutes a potentially useful intervention for the treatment of prolactinomas and that bioactive peptide gene delivery may open novel therapeutic avenues for the treatment of pituitary tumors.